Analisis Kinerja Keuangan Terhadap Price Earning Ratio (PER) - Muhamad Jusmansyah (Universitas Pamulang, 2020)
In investment activities an investor must have the ability to carry out stock analysis and one of the method who used to analyze a stock is fundamental analysis. According to that things, The intention to carry out a study is to be able to determinate The results of the balance sheet analysis have an impact PER in Public Companies Manufacturing Food and Beverages Sub Sector and research period is 2014-2018. This research uses four variable which are thought to effect PER is CR, DER, TATO, and ROE. This research used secondary data with total of sample is 12 companies. Purposive Sampling is method who used for this research. due to this analysis gives meaning ROE have a significant effect to PER while the variables CR, DER, and TATO have insignificant effect to PER. The Determination Coefficient is 0.534 which means that 53.4 % of PER is determinated by independent variable CR, DER, TATO, and ROE. While the remaining 0.466 or 46.6 % is explained by other variable outside the research